Case report: Mild phenotype of a patient with vascular Ehlers–Danlos syndrome and COL3A1 duplication mutation without alteration in the [Gly-X-Y] repeat sequence - Hayashi, Shujiro; Yamaguchi, Tomomi; Kosho, Tomoki; Igawa, Ken (Frontiers in Genetics, 2022)
Background: Vascular-type Ehlers–Danlos syndrome (vEDS) is an autosomal dominant inherited disorder caused by a deficit in collagen III as a result of heterogeneous mutations in the α1 type III collagen gene (COL3A1). Patients with vEDS often experience the first major complications in their early 20s, and >80% have at least one complication by the age of 40, which reduces the average life expectancy to 48 years. Most commonly, vEDS variants are heterozygous missense substitutions of a base-pair encoding a glycine (Gly) residue of the [Gly-X-Y] repeat of the COL3A1 protein. When a peptide chain derived from a mutant allele is present in the procollagen triple helical structure, the helical structure cannot be maintained. Therefore, typically, the mutated collagen peptide induces a dominant negative effect on procollagen production. Case presentation: A 58-year-old man developed a sudden disturbance of consciousness and abdominal pain, and was consequently taken to a nearby hospital, where an intra-abdominal aneurysm was found, in addition to mild small joint hypermobility and acrogeria. There has been no history of spontaneous pneumothorax, dislocation, or subcutaneous hematoma. Analysis of genomic DNA from a blood sample identified a likely pathogenic in-frame duplication mutation in the COL3A1 gene coding region. Interestingly this mutation is not expected to alter the [Gly-X-Y] triplet repeat sequence. We verified the pathogenicity of this mutation, according to the analysis of synthetic procollagen from cultured skin fibroblasts, electron microscopy, and mRNA expression analysis of unfolded protein response sensors for endoplasmic reticulum (ER) stress. Conclusion: Although clinical findings of the case were mild compared to typical vEDS, we could observe decreased α1 collagen III levels and morphological abnormalities of collagenous bundles in the patient samples compared with a normal control. Thus, this evidence supports the conclusion that this variant is a pathogenic variant. However, unlike the common vEDS, ER stress was not observed, and the mild phenotype presentation is suggested to be due to the unique mutation that permits the triple helix structure to be maintained to a certain extent.